Perfect secrets - Joyce, Brenda; Kane, Kathleen; O'Brien, Judith; Parr, Delia (New York : St. Martin's Paperbacks, 1999)
"From the foothills of east Taxes to the mossdraped riverbanks of Savannah, from a small town in upstate New York to the sun-baked terrain of the old west, four spectacular authors deliver romantic and unforgettable tales of scandals, deception and perfect secrets. Illusions will be shattered, lives will be changed--and nothing will ever be the same once they're revealed ... "--Cover.
Redemption / by Delia Parr
Keywords: Deception -- Fiction; Love stories